Shallow Geothermal Earth-to-Air Heat Exchange: Cooling and Heating for Sustainable Season Extension - Jaden Tatum; Tim McDermott; Ajay Shah (Urban Food Systems Symposium, 2024)
On-farm research collaborations between farmers and researchers can provide data-driven solutions that increase farm economic sustainability. Urban on-farm research is key in addressing production concerns that are specific to urban production, including heat island effects, intensive production pressure due to size constraints, and the need to develop high value specialty crops. Growing in protected environments like high tunnels, caterpillar tunnels, or hoop houses allow for season extension for urban food production which facilitates the production of crops that bring a higher price point. Non-electrified tunnels typically rely on passive ventilation and manual venting to manage internal conditions. To improve utility of high tunnels for season extension, additional capacity for ventilation and heating is needed, which can be a high cost to growers. Additionally, the most common options for high tunnel heating are propane-fueled heaters that have high operation costs and counteract sustainability efforts. One alternative that can provide both cooling capacity and heating at different parts of the year is a shallow geothermal earth-to-air heat exchanger (EAHX) that takes advantage of the soil’s insulating properties at shallow depths of 1 to 2 meters. These systems temper ventilation air, bringing it closer to soil temperatures, and direct it into the growing environment. This paper describes efforts to evaluate the efficacy of this EAHX infrastructure for season extension in Ohio through local partnerships and on-farm research sites. Initial findings from a pilot system installation indicates that these EAHX systems can be installed on-farm for prices competitive with propane-powered heaters, retrofit to existing high tunnels and caterpillar tunnels, and provide impactful heating and cooling, with BTU equivalent gains of 4 gallons a week of propane for heating in fall and cooling equivalent to ¼ ton air conditioning unit. This paper details EAHX system installations at both a rural and urban farm, including the installation at Franklinton Farms, a multi-parcel urban farm that has been growing since 2007 in the economically disadvantaged, poorly canopied neighborhood of Franklinton, immediately adjacent to downtown Columbus, Ohio, the 14th most populous city in the US. We will address lessons learned from the installations, the potential benefits, and costs of EAHX for season extension and fostering fruitful on-farm research partnerships.
Keywords: high tunnel; ventilation; heating; environmental control; season extension